Democratic economic policy - "Frey, Bruno S." (Oxford, 1983)
A task of great importance has been undertaken in this book. The search for a more democratic, responsive and effective way of making economic policy is a practical issue of great importance. Professor Frey has made a significant contribution to this endeavor and has fortunately expressed himself in language which the non-specialist can understand.
Keywords: Economic policy